Perception of quality of life of a cohort population years after relocation from previous low-dose radiation exposure in Co-60 contaminated buildings in Taiwan - Yen, Pimei Nancy; Yang, Chen-Chang; Chang, Peter Wushou; Hwang, Jing-Shiang; Lee, Hui-Chen; Kuo, Kuan-Liang; Lin, I-Feng (International journal of radiation biology, 2011)
Purpose: To evaluate measures of health-related quality of life in a cohort study in Taiwan to assess late health effects of protracted low-dose-rate γ-radiation exposure during 1982 to the mid-1990s. Materials and methods: In 2004, 1,407 cohort subjects were evaluated by a self-measured World Health Organisation - Brief quality of life Questionnaires (WHOQOL-BREF Taiwan version) during an annual medical check-up in a hospital. Results of their health-related quality of life (HRQoL) in physical, psychological, social relationship and environmental domains were compared with an unexposed reference population in the same city. Results: The exposed population was shown to have significantly lower quality of life (QOL) scores in physical, psychological and social relationship domains, but not in the environmental domain compared to the unexposed population. These findings were observed in all age groups with the greatest decrease found among those younger than 25 years old. Female subjects were shown to have larger decrease than male subjects. Conclusions: More than 10 years after being informed of radiation exposure, the exposed populations were observed to have significantly lower perception of HRQoL even though no biomedical effects were apparent. It is recommended that appropriate intervention be carried out in the follow-up of post-event rehabilitation for the radiation exposed.